Reversed Phase HPLC Estimation of Lansoprazole in Pure and Pharmaceutical Formulations - Prasada Rao, K.V.S.; Vijaya Kumar, G.; Vijaya Kumari, K.; Srinivas, L.D.; Prabhakar, G. (Asian Journal of Chemistry, 2010)
A simple, rapid and sensitive high performance liquid chromatographic method for the deternation of lansoprazole in pharmaceutical formulations. The separation was achieved by using column Partisil, ODS, C18 (150 x 4.6, 5 μ) and a mobile phase consisting of methanol : KH2PO4 (pH 2.5), (60:40, v/v), a flow rate of 1.0 mL /min and UV detection at 240 nm. The detection and quantitative lits were 0.05 μg/mL and 0.15 μg/mL respectively, while the linear range of detection was between 0.1 and 100 μmg/mL. The method has been applied successfully to the deternation of Lansoprazole in pharmaceutical formulations.